OPTIMISASI MATRIKS BOBOT PADA LINEAR QUADRATIC REGULATOR (LQR) INVERTED PENDULUM MENGGUNAKAN ANT COLONY OPTIMIZATION - Dinita Rahmalia (Prodi Matematika FMIPA Unirow Tuban, 2019)
Inverted pendulum consists of cart and pendulum attached in it. The force is given to the system consists of angle position, angle velocity, cart position, and cart velocity. The objective function of inverted pendulum is minimizing pendulum angle and cart position following trajectories so that pendulum is stable. The model of optimal control used in this research is applying Linear Quadratic Regulator (LQR). In LQR, the value of objective function is determined by weight matrices and weight matrices are generally approached by trial and error. Ant Colony Optimization (ACO) is optimization method based on behavior of ants in searching path from home towards to food source. The simulation results show that ACO method can find optimal weight matrices minimizing performance index as objective function.